Avoidance of food effect on oral absorption profile of itraconazole by self-micellizing solid dispersion approach. Issue 5 (October 2017) - Kojo, Yoshiki; Kobayashi, Kanako; Matsunaga, Saori; Suzuki, Hiroki; Seto, Yoshiki; Sato, Hideyuki; Onoue, Satomi
Abstract: The present study was aimed to avoid pharmacokinetic transitions of itraconazole (ITZ) evoked by high-fat meal intake by employing a self-micellizing solid dispersion (SMSD) approach. The dissolution behavior of SMSD/ITZ was assessed in simulated gastric fluid (SGF) and simulated intestinal fluid (SIF). To evaluate the food effect on the oral absorption profile of ITZ, a pharmacokinetic study was conducted on orally-dosed ITZ samples in fasted and high-fat meal-fed rats. Crystalline ITZ showed a 9.0-fold higher dissolution amount of ITZ in fed-state SGF (FeSSGF) than in fasted-state SGF (FaSSGF), whereas there was no significant difference in the dissolution amount of ITZ in SMSD/ITZ between FeSSGF and FaSSGF. In fed- and fasted-state SIF, SMSD/ITZ exhibited reduced variation of ITZ dissolution, possibly leading to suppression of the food effect on the dissolution behavior of ITZ. After the oral administration of crystalline ITZ to high-fat meal-fed rats, the oral bioavailability of ITZ was 14-fold higher than that in fasted rats. In contrast, orally-dosed SMSD/ITZ in fed rats exhibited limited transition of pharmacokinetic behavior regardless of food intake due to the improvement in the dissolution behavior of ITZ even under fasted conditions. SMSD technology could be an efficacious dosage option for the consistent oral absorption and clinical outcomes of ITZ. Graphical abstract: